Integration of administrative records for social protection policies: Contributions from the Brazilian experience - Letícia Bartholo; Joana Mostafa; Rafael Guerreiro Osorio (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Integrating information for the purpose of articulating social protection policies is hard work. It requires a combination of political will, capacity for institutional cooperation, software development and direct communication channels with citizens. Because of this complexity, countries that pursue this objective often cooperate to exchange knowledge, and the Brazilian Single Registry (Cadastro Único), the backbone of some 20 social protection programmes, is frequently cited as a successful example of integration. By sharing the experience of the Single Registry, this text discusses some of the essential elements required to design and operate such instruments of social policy integration. It brings to light some of the challenges that are still being faced to fulfil the promise of greater integration among social protection programmes and to provide greater ease of access and respect to citizens. [...]
Keywords: 330; Cadastro Único; Bolsa Família programme; Single Registry; assistance; entitlements; family allowances; means testing; poverty alleviation; public assistance; safety net; social welfare programmes; SSI; transfer payments; transfers; welfare effects; welfare policy; welfare programme; welfare provision; work welfare